2018
DOI: 10.3892/ol.2018.8072
|View full text |Cite
|
Sign up to set email alerts
|

SRSF7 knockdown promotes apoptosis of colon and lung cancer cells

Abstract: Serine/arginine-rich (SR) proteins are a family of important splicing factors, which are involved in multiple aspects of RNA processing, including splicing, mRNA nuclear export, mRNA stability and translation. Previous studies have identified a number of SR proteins that exhibit abnormal expression in various tumor types. In the present study, the expression and function of serine/arginine-rich splicing factor 7 (SRSF7) were investigated in colon and lung cancer. Using tissue immunohistochemistry, it was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 30 publications
3
28
0
Order By: Relevance
“…Song et al also observed that the level of SRSF7 was upregulated in NSCLC tissues, meanwhile, the expression level of SRSF7 was negatively correlated with miR-374b-5p and positively correlated with MALAT1. Overexpression of SRSF7 could reverse the effects of MALAT1 knockdown on proliferation, apoptosis, and invasion in NSCLC cells [47]. In addition, SRSF1 was found to be upregulated in colon, kidney, lung, liver, pancreas and breast tumour [18,20,48,49].…”
Section: Abnormal Expression Of Srs and Cancermentioning
confidence: 92%
“…Song et al also observed that the level of SRSF7 was upregulated in NSCLC tissues, meanwhile, the expression level of SRSF7 was negatively correlated with miR-374b-5p and positively correlated with MALAT1. Overexpression of SRSF7 could reverse the effects of MALAT1 knockdown on proliferation, apoptosis, and invasion in NSCLC cells [47]. In addition, SRSF1 was found to be upregulated in colon, kidney, lung, liver, pancreas and breast tumour [18,20,48,49].…”
Section: Abnormal Expression Of Srs and Cancermentioning
confidence: 92%
“…The SRSF6 is involved in the abnormal alternative splicing of the corticotropin-releasing hormone receptor type 1 (CRH-R1) causing indirect perturbation of oncogenic kinases, such as p38 MAPK, Akt and GSK3β, and accumulation of β-catenin in breast cancer (Lal et al, 2013). Knockdown experiments of SRSF7 in HCT116 colon and A549 lung cancer cell lines revealed the production of an exon 6-lacking isoform of the Fas receptor mRNA, that promotes cell survival (Fu and Wang, 2018).…”
Section: Oncogenic Functions Of Hnrnps and Srsfsmentioning
confidence: 99%
“…SRSF7 contains a motif with function of recognizing speci c RNAs at the N-terminus and a structure with function of facilitating spliceosome assembly, and based on this, SRSF7 participates in alternative splicing processes of multiple pre-mRNAs [23] . So far SRSF7 is known to express abnormally and play regulatory roles in multiple cancers including lung cancer, kidney cancer and colon cancer [7,23,24] . In this study, based on the TCGA database, we found for the rst time that SRSF7 was highly expressed in glioma tissues and cells, especially in high grade.…”
Section: Discussionmentioning
confidence: 99%